Docetaxel, Cisplatin, and 5‐Fluorouracil as perioperative chemotherapy compared with surgery alone for resectable gastroesophageal adenocarcinoma. (11th October 2016) - Fiteni, Frédéric; Paget‐Bailly, Sophie; Messager, Mathieu; N'Guyen, Thierry; Lakkis, Zaher; Mathieu, Pierre; Lamfichekh, Najib; Picard, Alain; Benzidane, Bilell; Cléau, Denis; Bonnetain, Franck; Borg, Christophe; et al.
Abstract: Docetaxel, cisplatin, and 5‐fluorouracil (DCF) significantly improved overall survival in metastatic gastroesophageal adenocarcinoma (GEA). The aim of this study was to assess efficacy of DCF regimen as perioperative chemotherapy compared with surgery alone in patients with resectable GEA. We identified 789 patients who underwent surgery alone and 62 patients who received at least one cycle of DCF regimen consisting of docetaxel (75 mg/m 2 on day 1), cisplatin (75 mg/m 2 on day 1), and 5‐fluorouracil (750 mg/m 2 /day on continuous perfusion on days 1 to 5), every 3 weeks. Overall survival was compared using Cox proportional hazards regression model with adjustments for confounding factors provided by two propensity score methods: inverse probability of treatment weighting (IPTW) and matched‐pair analysis. In Cox multivariate analysis weighted by IPTW, DCF group was associated with favorable overall survival (OS) compared with the surgery group (HR = 0.59; 95% CI, 0.45–0.78; P = 0.0003). For the matched‐pair analysis (comparing 41 patients for each group with the same baseline characteristics), median OS was 22 months and 57 months for the surgery group and DCF group, respectively (log‐rank P = 0.0011). In Cox multivariate analysis, DCF group was associated with favorable OS compared with the surgery group (HR = 0.29; 95% IC, 0.14–0.64; P = 0.0019). In the matched‐pair population, major complications (Dindo‐Clavien grade 3–5) arose in six patients (14.63%) in the DCF group and seven patients (17.07%) in the surgery group ( P = 1). Perioperative DCF chemotherapy is superior to surgery alone in terms of OS. A randomized phase III trial should compare DCF to standard perioperative regimens. Abstract : Perioperative Docetaxel, cisplatin, and 5‐fluorouracil (DCF) chemotherapy is superior to surgery alone in terms of overall survival. A randomized phase III trial should compare DCF to standard perioperative regimens.